Xiangshao granules can relieve emotional symptoms in menopausal women: a randomized controlled trial. (4th May 2021) - Chen, R.; Tang, R.; Zhang, S.; Wang, Y.; Wang, R.; Ouyang, Y.; Xie, X.; Liu, H.; Lv, S.; Shi, H.; Zhang, Y.; Xie, M.; et al.
Abstract: Objective: This study aimed to investigate the safety and efficacy of Xiangshao granules for treating emotional disorders in perimenopausal and postmenopausal women. Methods: The current investigation was a double-blind, randomized, placebo-controlled, multicenter trial that included 300 perimenopausal and postmenopausal Chinese women aged 40–60 years. Participants received either a placebo ( n  = 150) or Xiangshao granules ( n  = 150) for 8 weeks. Outcome measures included Hamilton Depression Rating Scale (HAMD) and Hamilton Anxiety Rating Scale (HAMA) scores, which were assessed at baseline, 4 weeks, and 8 weeks. The primary efficacy variables were changes in HAMD and HAMA scores after 8 weeks. Results: After 8 weeks, the mean HAMD scores decreased from 15.0 to 7.9 in the Xiangshao group and from 16.3 to 10.0 in the placebo group, and the respective mean reductions in HAMA scores were from 16.0 to 8.5 and from 17.1 to 10.9. Clinical improvements in symptoms of both depression and anxiety after 8 weeks differed significantly in the two groups ( p  < 0.05). The cure rate was significantly higher in the Xiangshao group. There were no significant differences in the rates of adverse events in the two groups. Conclusions: Xiangshao granules can relieve symptoms of depression and anxiety significantly and safely.